Typifications of 31 names in Azorella (Azorelloideae, Apiaceae) from South America - Fernández, Martina; Martínez, Susana Graciela; Calviño, Carolina Isabel (Phytotaxa, 2020)
The genus Azorella, as currently circumscribed, with 58 species, is taxonomically complex. Therefore, the typification of its names is particularly important for the correct delimitation of its species. Recent taxonomic revisions within the group contributed to the nomenclature in this respect, but as part of the studies for the Flora of Argentina project, many names in Azorella still need typifications. To resolve typifications, protologues and available original material for all names were studied, and decisions were made following the International Code of Nomenclature for algae, fungi, and plants, and based on our expertise on the taxonomy of the group. As a result, 27 lectotypes, and 4 neotypes are designated here.